Inovasi Pembelajaran Berbasis Digital dalam Meningkatkan Kualitas Pendidikan - Firdaus, Muhammad (Universitas Islam Zainul Hasan Genggong, 2025)
The development of digital technology has brought significant impact in the world of education. Digital-based learning innovation becomes a solution in improving the effectiveness and efficiency of the teaching and learning process. teaching and learning process. This article discusses the role of technology in education, digital digital learning innovations that have been implemented, as well as the challenges faced in their implementation. implementation. By using literature study method, this research examines various digital learning models, including flipped classroom, gamification, and the utilization of artificial intelligence (AI) in classroom, gamification, and the utilization of artificial intelligence (AI) in education. education. The results show that technology can increase student engagement, improve engagement, improve learning outcomes, and open wider access to education. access to education. However, technology gaps and educator readiness are the main challenges in its implementation. the main challenge in its implementation. Therefore, support is needed for infrastructure and training for educators to optimize the implementation of digital-based learning.